2021
DOI: 10.1182/bloodadvances.2021005220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of daratumumab combined with all-transretinoic acid in relapsed/refractory multiple myeloma

Abstract: The efficacy of daratumumab is partially dependent on CD38 expression on multiple myeloma (MM) cells. We have previously shown that ATRA upregulates CD38 expression and reverts daratumumab-resistance ex vivo. We therefore evaluated the optimal dose, efficacy and safety of daratumumab combined with ATRA in daratumumab-refractory MM patients in a phase 1/2 study (NCT02751255). In part A of the study, 63 patients were treated with daratumumab monotherapy. Fifty daratumumab-refractory patients were subsequently en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…The proteasome inhibitor, bortezomib, is approved for multiple myeloma treatment [ 27 ]. RAR agonists have been intensively studied in the same indication with promising results [ 28 , 29 , 30 ], suggesting a beneficial dual mode-of-action for bortezomib. Interestingly, sensitization of myeloma cells to proteasome inhibitors by concomitant retinoic acid treatment has recently been reported [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proteasome inhibitor, bortezomib, is approved for multiple myeloma treatment [ 27 ]. RAR agonists have been intensively studied in the same indication with promising results [ 28 , 29 , 30 ], suggesting a beneficial dual mode-of-action for bortezomib. Interestingly, sensitization of myeloma cells to proteasome inhibitors by concomitant retinoic acid treatment has recently been reported [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that anti-CD38 immunotherapies, either CAR T cells or antibodies, are effective for cancers with high CD38 expression. The toxicity of ATRA alone [ 37 ] or in combination with arsenic trioxide [ 38 ] or anti-CD38 antibody [ 39 ] is acceptable. Thus, our data broaden the potential clinical use of anti-CD38 immunotherapies to treat CD38 high lymphoid cancer cells and support the combinations with ATRA to treat CD38 low cancers that are sensitive to ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, anti-CD38 immunotherapies with ATRA may not be the next best option for rituximab-resistant DLBCL. A recent clinical trial tested the efficacy and safety of daratumumab combined with ATRA in R/R MM patients, yet the addition of ATRA and intensification of daratumumab had limited activity [ 39 ]. Thus, caution must be exercised when evaluating the clinical benefit of anti-CD38 and ATRA to patients with lymphoid neoplasms, particularly for R/R patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 However, in the most recent study, Frerichs et al found that the increased efficacy associated with the addition of ATRA was limited and temporary due to the transient nature of the upregulation of CD38 expression. 61 …”
Section: Discussionmentioning
confidence: 99%